Digital Literacy and Development of Santripreneur Asset Quality Through The Leadership Role of Kyai: A Case Study of Islamic Boarding Schools (Journal of Private and Commercial Law, 2022)
Islamic boarding schools in the current global era need to increase their capacity as Islamic educational institutions that have advanced civilizations. With the emergence of global developments regarding economic conditions in ASEAN countries (within the scope of Southeast Asia), one of which is marked by the presence of the AEC (ASEAN Economic Community), the Indonesian people must improve their soft skills amid the global market competition to be competitive. Islamic boarding schools need to respond to global challenges so that Islamic values do not fade with the incessant development of industrial and economic globalization. This study aims to analyze the implementation of the Law on Information and Electronic Transactions in the use of electronic media in Islamic boarding schools and analyze Kyai’s strategy in empowering santri entrepreneurship and government support in the role of Islamic boarding schools as a catalyst for the community’s economy. This collaborative research for community service is located in Batang Regency. The results show that in facing the disruptive era, Islamic boarding schools in addition to implementing Islamic values in the use of digital media, it is necessary to socialize the Law on Information and Electronic Transactions to santri so that they can provide a borderline in the use of digital media following applicable regulations apply in Indonesia. Islamic boarding schools have the potential for economic empowerment, considering that many Islamic boarding schools have built cooperatives, developed various business units or small and medium-sized industries, and have a cubator business. The government develops entrepreneurship in Islamic boarding schools with the program “One Islamic Boarding School One Product”.